Benefits of Family Meals - Varnessa McCray; Victor W. Harris; Martie Gillen (EDIS)
Over the past 30 years obesity among children has increased. One way to help youth make healthy food choices is by creating healthy eating choices and habits at home, starting with family meals. When parents value family dinners, children are likely to view family dinners as important. Family meals can provide important examples to show children what foods are good to eat and how much of the good foods they should eat. This 5-page fact sheet was written by Varnessa McCray, Victor W. Harris, and Martie Gillen, and published by the UF Department of Family Youth and Community Sciences, April 2013.